2013
DOI: 10.1074/jbc.m113.466854
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium smegmatis Lhr Is a DNA-dependent ATPase and a 3′-to-5′ DNA Translocase and Helicase That Prefers to Unwind 3′-Tailed RNA:DNA Hybrids

Abstract: Background: Helicases play important roles in nucleic acid transactions. Results: Mycobacterial Lhr uses the energy of ATP hydrolysis to drive 3Ј-to-5Ј translocation along single strand DNA and to unwind duplexes en route. Conclusion: Lhr is better at unwinding an RNA:DNA hybrid than a DNA:DNA duplex. Significance: Lhr defines a novel clade of helicases with a signature domain organization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
59
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(66 citation statements)
references
References 29 publications
7
59
0
Order By: Relevance
“…The Lhr helicases were first discovered in 1995 as the longest helicase related protein (Lhr); studies showed that Lhr is a non-essential gene in E.coli (Reuven et al, 1995). This helicase remains unstudied until 2013, a recent work from Mycobacterium smegmatis exemplified Lhr as a novel clade of SF2 helicases that was proven by its biochemical specificities and signature domain organization (Reuven et al 1995, Ordonez et al 2013. …”
Section: Accepted Manuscriptmentioning
confidence: 97%
“…The Lhr helicases were first discovered in 1995 as the longest helicase related protein (Lhr); studies showed that Lhr is a non-essential gene in E.coli (Reuven et al, 1995). This helicase remains unstudied until 2013, a recent work from Mycobacterium smegmatis exemplified Lhr as a novel clade of SF2 helicases that was proven by its biochemical specificities and signature domain organization (Reuven et al 1995, Ordonez et al 2013. …”
Section: Accepted Manuscriptmentioning
confidence: 97%
“…In all of our helicase assays, we found that EcDinG was able to display optimal activity between 10 and 25 nM protein, but MtDinG required Ͼ100 nM protein (substrate/ protein ratio of 1:200). However, it has been shown that mycobacterial enzymes require Ͼ100 nM protein for its optimal activity (32)(33)(34)(35).…”
Section: Cloning and Purification Of M Tuberculosis Ding-e Colimentioning
confidence: 99%
“…Several of the most commonly used methods of monitoring the translocation of a motor protein are: a) measuring the arrival of the protein at a particular point along the DNA (19)(20)(21)(22)(23)(24); b) detecting the displacement of obstacles from DNA by the translocating motor (25)(26)(27); c) DNA-dependent ATPase activity of the motor (18,22,(27)(28)(29)(30)(31); d) translocation-induced changes in the structure/ topology of the DNA (32,33). While each approach has advantages and disadvantages, addressing the key questions typically involves a combined approach of several of these techniques.…”
Section: Experimental Approaches and Mechanistic Modelsmentioning
confidence: 99%
“…For example, many motors are believed to form DNA loops during translocation (22)(23)(24)(25)(26). By considering motor efficiency, the distinction between kinetic and physical step-sizes of the translocation mechanism can be elucidated.…”
Section: Introductionmentioning
confidence: 99%